Pengaruh Tingkat Pendidikan dan Pengalaman Kerja terhadap Kinerja Karyawan Dimediasi Motivasi Kerja Pada Dealer Honda Sumenep - Khofifah Mamluatur Riskiyah; Fathorrahman; Mohammad Rofik (Universitas PGRI Adi Buana, 2025)
Employee performance plays an important role in maintaining competitive advantage, especially in service-oriented industries such as the automotive sector. This study aims to examine the effect of education level and work experience on employee performance, with work motivation as a mediating variable. This study employs a quantitative approach with an explanatory design. Data were collected through a survey of 95 respondents working in the automotive services sector and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The analysis results indicate that educational level does not significantly influence employee performance but has a positive effect on work motivation. Conversely, work experience significantly influences performance but does not directly affect work motivation. Motivation was found to be a significant mediating variable between work experience and performance but did not mediate the relationship between education and performance. These findings suggest that work experience, when combined with motivational drive, can enhance performance more substantially than relying solely on educational background. Practical implications emphasize the importance of developing human resource management systems focused on optimizing motivation and accumulating functional experience as productive organizational assets.